Pengaruh Brand Image, Peer Group Dan Physical Evidence Terhadap Minat Sekolah Ke Perguruan Tinggi di Kota Serang Tahun 2022 - Dhany Isneni D. (Pusat Riset dan Inovasi Nasional, 2022)
Education should be a center of attention in Indonesia, education services for the community, must continue at the level throughout the country. Implementation and service of education in Indonesia is still uneven, still focused on big cities. Many areas in Indonesia find it difficult for the public to obtain educational services, Jakarta as the national capital, as if everything is there and available there, but it must be admitted for Banten Province which is adjacent to the Special Capital Region of Jakarta. Data from the Central Statistics Agency (BPS) for 2016, shows that the average length of schooling in the Banten region is only 8.37 years, in Serang District some students have to risk their lives because the school is damaged, so that classrooms are used alternately. Based on data released by the Ministry of Culture and Culture, there are 48% of schools in Banten that have been damaged and are not suitable for normal use as school rooms. The Banten Education Office stated that there are many problems driving the low net enrollment rate (APM) in schools in Banten, including inadequate facilities and infrastructure, educational services are not evenly distributed, and the community's level of education is still low. This research is intended to identify and examine the existence of the image of higher education, peers and facilities and infrastructure in influencing students' interest in continuing their education to a higher level. The method used in this study is a quantitative method with descriptive and verification properties. The analysis tool used is path analysis with the help of the SPSS for Windows 25 program. The results of the study show that there is an influence from the image of higher education, peers and facilities and infrastructure on interest in college.